PERSONALIZED MEDICINE: FROM SCIENCE TO PRACTICE - Nikitin, A G (Kliničeskaâ praktika, 2016)
In 2012, in Federal research and clinical centre of FMBA of Russia the laboratory of genetics was established, which conducts scientific research in the field of genetic predisposition to socially significant diseases, early diagnosis of oncopathology, as well as methods for processing genomic data. Significant experience in molecular genetic testing have allowed to help to implement a routine practice of a multiprofile hospital modern methods of genetic analysis that were previously available only to large specialized centers.